Application of in-situ growth three-dimensional ZIF-8 / MXene composite material in preparation of zinc-iodine battery
By growing ZIF-8 nanometer particles on the surface of MXENE, a three-dimensional ZIF-8/MXENE composite material is formed, which solve the problem of zinc negative chief crystals and corrosion problems in zinc iodine batteries, and realizes zinc tolerance and long cyclic life. negative electrode.
Patent Information
- Application Number
- CN202411493749.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-24
AI Technical Summary
The zinc negative electrode in zinc-iodine batteries will produce dendrites due to uneven electric field distribution, resulting in short circuits, and hydrogen evolution reactions are prone to occur in aqueous electrolytes, resulting in corrosion.
By growing ZIF-8 nanometer particles in situ on the surface of the MXENE, a three-dimensional ZIF-8/MXENE composite material is formed as a protective coating attached to the surface of the zinc electrode to prevent MXENE from gathering and improving electrochemical performance.
Effectively prevent MXENE from gathering, improve the corrosion resistance and cycle stability of zinc negative electrode, extend the cycle life of zinc iodine batteries, and increase the capacity maintenance rate of the battery.
Smart Images

Figure CN119361718A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional coatings, and specifically relates to an application of an in-situ grown three-dimensional ZIF-8 / MXene composite material in the preparation of a zinc-iodine battery. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Aqueous rechargeable batteries have significant advantages in large-scale energy storage, such as easy assembly, high safety and low price, and therefore have broad application prospects. Among various types of aqueous batteries, zinc-based batteries stand out due to their high theoretical capacity, low redox potential and abundant natural resources. However, the zinc negative electrode will produce dendrites due to uneven electric field distribution, and may even pierce the battery separator, causing a short circuit. In addition, the zinc negative electrode is prone to hydrogen evolution reaction in aqueous electrolytes, resulting in a local increase in pH, which in turn corrodes the surface of the zinc negative electrode.
[0004] To address these issues, researchers have explored various strategies, including three-dimensional structural engineering, surface modification, electrolyte optimization, and separator modification. Among these methods, surface modification has become one of the most effective methods due to its ease of operation, excellent scalability, and potential to improve the performance of zinc anodes. In particular, MXenes, as a class of two-dimensional transition metal carbides and / or nitrides, have attracted widespread attention. MXenes have M n+1 X n T x The general formula, wherein M represents a transition metal, X represents carbon and / or nitrogen, T x Indicates the surface terminal groups (such as -F, -O, -OH). 2+ The uniform deposition of ions has significant advantages, which is crucial to reducing dendrite formation and improving the overall performance of zinc batteries (corrosion resistance, conductivity, cycle stability, etc.). Therefore, the rational design of composite materials to avoid MXenes aggregation is crucial for the synthesis of stable coatings and is an urgent problem to be solved by technicians in this field. Iodine is abundant in seawater, and aqueous zinc-iodine batteries have become a new type of energy storage device. It is of great strategic significance to modify the zinc negative electrode and apply it to zinc-iodine batteries. Summary of the invention
[0005] In response to the needs of the prior art, the purpose of the present invention is to provide an in-situ grown three-dimensional ZIF-8 / MXene composite material for use in the preparation of zinc-iodine batteries, by utilizing the synergistic properties of MXenes and metal organic framework compounds (MOFs) to improve the zinc negative electrode. The in-situ growth of ZIF-8 nanoparticles on the MXene surface can not only prevent aggregation but also improve the electrochemical performance, providing a promising strategy for the development of reversible zinc negative electrodes with corrosion resistance, long cycle life and high capacity.
[0006] Specifically, the present invention provides the following technical solutions:
[0007] In a first aspect of the present invention, a method for preparing a zinc-iodine battery by using an in-situ grown three-dimensional ZIF-8 / MXene composite material is provided, wherein a slurry prepared by using the composite material and a binder is attached to the surface of a zinc electrode as a protective coating;
[0008] The composite material consists of MXene two-dimensional nanosheets and ZIF-8 nanoparticles, and the ZIF-8 nanoparticles are uniformly distributed on the MXene two-dimensional nanosheets.
[0009] Preferably, the binder is selected from one or more of sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylonitrile, polyvinyl alcohol, polytetrafluoroethylene, polyvinylidene fluoride, and polyimide; further preferably, the binder is polyvinylidene fluoride (PVDF).
[0010] Preferably, the method for preparing the in-situ grown three-dimensional ZIF-8 / MXene composite material comprises the following steps:
[0011] S1, adding MAX powder into etching solution to perform etching reaction to obtain MXene dispersion;
[0012] S2, adding ZIF-8 nanoparticles to the MXene dispersion to obtain a composite material (ZIF-8 skeleton-modified MXene two-dimensional nanosheets ZIF-8@MXene);
[0013] S3, mixing the composite material and the binder, coating the obtained slurry on the electrode sheet, and drying to obtain the slurry.
[0014] Preferably, in step S1, the MAX powder is selected from one or more of Ti3AlC2, V2AlC and Nb2AlC; and the etching solution is selected from one or more of HF, HCl and LiF.
[0015] Preferably, in step S1, the temperature of the etching reaction is 30-50° C., and the time is 12-36 hours; further preferably, the temperature of the etching reaction is 40° C., and the time is 24 hours.
[0016] Preferably, in step S1, the mixture obtained after the etching reaction is washed with ultrapure water and ultrasonically stripped in sequence to obtain a MXene suspension, and then centrifuged to obtain a MXene dispersion;
[0017] The pH value of the mixture after washing with ultrapure water is neutral;
[0018] The specific operation of the ultrasonic stripping is: under nitrogen protection, the neutral mixture after washing with ultrapure water is placed in an ice water bath and ultrasonicated for 0.8 to 1.2 hours; preferably, the ultrasonic time is 1 hour;
[0019] The centrifugal speed is set at 3000-5000 rpm; preferably, the speed is set at 4200 rpm.
[0020] Further preferably, the MXene dispersion is freeze-dried to obtain solid MXene two-dimensional nanosheets; the freeze-drying temperature is -50 to -70°C, and the time is 20 to 50 hours; preferably, the freeze-drying temperature is -60°C, and the time is 30 hours.
[0021] Preferably, in step S2, the ZIF-8 nanoparticles are prepared by mixing a 2-methylimidazole aqueous solution with a Zn(NO3)2·6H2O aqueous solution, followed by washing, centrifugation, and freeze-drying;
[0022] Wherein, the molar ratio of Zn(NO3)2·6H2O to 2-methylimidazole is 1:30 to 1:80; preferably, the molar ratio of Zn(NO3)2·6H2O to 2-methylimidazole is 1:50;
[0023] The mixing reaction time is 2 to 5 hours; preferably, the mixing reaction time is 4 hours;
[0024] The freeze-drying temperature is -50 to -70°C, and the time is 20 to 50 hours; preferably, the freeze-drying temperature is -60°C, and the time is 30 hours.
[0025] Preferably, in step S2, the composite material is prepared by first adding 2-methylimidazole to a MXene dispersion, then mixing and reacting with a Zn(NO3)2·6H2O aqueous solution, and then washing, centrifuging, and freeze-drying in sequence;
[0026] Wherein, the mass ratio of the MXene dispersion to 2-methylimidazole is 20:1 to 50:1; further preferably, the mass ratio of the MXene dispersion to 2-methylimidazole is 35:1;
[0027] The mixing reaction time is 2 to 5 hours; preferably, the mixing reaction time is 4 hours;
[0028] The freeze-drying temperature is -50 to -70°C, and the time is 20 to 50 hours; preferably, the freeze-drying temperature is -60°C, and the time is 30 hours.
[0029] Preferably, in step S3, the mixed composite material and binder are added to an organic solvent to form a slurry, which is then coated on the electrode sheet; further preferably, the organic solvent is N-methyl-2-pyrrolidone.
[0030] Preferably, in step S3, the mass ratio of the composite material to the binder is 10:1 to 8:1, preferably 9:1.
[0031] Preferably, in step S3, the coating thickness is 10 μm, and a drying treatment is performed after coating, specifically: under vacuum conditions, the coated electrode is dried at 55 to 65° C. for 15 to 30 hours; further preferably, the coated electrode is dried at 60° C. for 24 hours.
[0032] Preferably, in step S3, the diameter of the electrode sheet is 8 to 10 mm, more preferably 10 mm.
[0033] A second aspect of the present invention provides a battery negative electrode, which includes an in-situ grown three-dimensional ZIF-8 / MXene composite material and a binder.
[0034] Preferably, the slurry prepared by the in-situ grown three-dimensional ZIF-8 / MXene composite material and the binder is coated on the zinc foil as a protective coating; the mass ratio of the composite material to the binder is 10:1 to 8:1, preferably 9:1.
[0035] The third aspect of the present invention provides a zinc-iodine battery, comprising the battery negative electrode described in the second aspect, and also comprising a positive electrode sheet, a separator and an electrolyte.
[0036] Preferably, the preparation method of the positive electrode sheet is specifically as follows: aniline is added to a phytic acid aqueous solution, and an oxidant aqueous solution is added to the obtained aniline phytic acid aqueous solution to cause a polymerization reaction to obtain a black porous carbon material PCM-NP co-doped with N and P; then the PCM-NP is mixed with iodine for heating reaction to obtain iodine-loaded PCM-NP, which is mixed with a conductive agent and a binder and rolled into an electrode sheet to obtain;
[0037] Wherein, the volume ratio of the phytic acid aqueous solution to the aniline is 4:1; the volume ratio of the aniline phytic acid aqueous solution to the oxidant aqueous solution is 5:1;
[0038] The polymerization reaction temperature is 3-5°C and the reaction time is 12-36h;
[0039] The product after the polymerization reaction is washed and then subjected to high-temperature pyrolysis, wherein the pyrolysis temperature is 800-1200° C. and the time is 1-5 hours;
[0040] The mass ratio of the black porous carbon material PCM-NP to iodine is 1:1 to 4:1, preferably 2:1;
[0041] The heating reaction temperature is 100-150°C and the time is 4-8h;
[0042] The mass ratio of the iodine-loaded PCM-NP, the conductive agent and the binder is 7-8:1-2:0.8-1.2; preferably 7.5:1.5:1;
[0043] Further preferably, the oxidant is any one of persulfate or peroxide; the persulfate is any one of ammonium persulfate, sodium persulfate, potassium persulfate, manganese persulfate, potassium hydrogen persulfate or potassium peroxymonosulfonate; and the peroxide is hydrogen peroxide or peracetic acid.
[0044] The beneficial effects achieved by one or more of the above technical solutions of the present invention are as follows:
[0045] (1) The present invention proposes to in situ grow ZIF-8 nanoparticles on the MXene surface, which can not only prevent the MXene aggregation phenomenon but also improve the electrochemical performance, providing a promising strategy for the development of reversible Zn anodes with long cycle life and high capacity.
[0046] (2) The zinc anode sheet coated with ZIF-8@MXene prepared in the present invention has excellent performance in a symmetrical battery at a current density of 1 mA cm -2 The cycle life exceeds 1050h; when assembled into a full battery with iodine-loaded polyaniline positive electrode, an ultra-long life of 2400 cycles is achieved.
[0047] (3) The ZIF-8@MXene coating prepared in the present invention has excellent corrosion resistance. The corrosion potential of Z@M-Zn (-0.972 V vs Ag / AgCl) is significantly higher than that of bare zinc (-0.983 V vs Ag / AgCl), MXene-Zn (-0.980 V vs Ag / AgCl), ZIF-8-Zn (-0.975 V vs Ag / AgCl) and ZIF-8 / Ti3C2T x -Zn (-0.978 V vs Ag / AgCl), and the corrosion current of Z@M-Zn (0.25 mA cm -2 ) is significantly lower than the other four electrodes (bare zinc is 2.1 mA cm -2 MXene-Zn is 1.58 mA cm -2, ZIF-8-Zn is 0.65 mA cm -2 ,ZIF-8 / Ti3C2T x -Zn: 1.37 mA cm -2 ).
[0048] (4) The contact angle test of the coating was carried out in the present invention. The results showed that there was no significant difference between MXene-Zn (75.8°) and ZIF-8-Zn (69.8°) and bare zinc. However, after the two were composited, the contact angle changed significantly (95.6°), which increased significantly. This indicates that the hydrophobicity of Z@M-Zn in the electrolyte was significantly enhanced, thereby improving the corrosion resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0050] Figure 1 The SEM image (a) of Ti3AlC2 of the present invention; the TEM image (b) of MXene;
[0051] Figure 2 XRD diagram of MXene before and after etching of the present invention;
[0052] Figure 3 The SEM and TEM images of Z@M of the present invention are shown in FIG.
[0053] Figure 4 is the element distribution diagram of Z@M of the present invention;
[0054] Figure 5 Tafel test and the corresponding corrosion current density bar graph;
[0055] Figure 6 The contact angle test of the coatings prepared in Example 1 and Comparative Examples 1 to 3 of the present invention;
[0056] Figure 7 It is a linear sweep voltammetry test;
[0057] Figure 8 Coulombic efficiency test of asymmetric battery (3mA cm -2 ,1.5mAh cm -2 );
[0058] Fig. 9 For long cycle test of symmetrical battery (1mA cm -2 ,1mAh cm -2 );
[0059] Fig.10Long cycle tests were carried out on a full battery assembled with Z@M-Zn anode and iodine-loaded polyaniline. DETAILED DESCRIPTION
[0060] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0061] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0062] Example 1 :This embodiment provides a protective coating for zinc-iodine batteries and a preparation method thereof
[0063] (1) Synthesis of Ti3C2T x MXene dispersion: Add 30 mL of 9M hydrochloric acid solution and 2 g of LiF powder to a polytetrafluoroethylene reaction container and mix thoroughly to form a uniform solution. Slowly add 1.5 g of Ti3AlC2 powder to the solution and keep it at 40 °C for 24 h. After etching, wash with ultrapure water until neutral and ultrasonicate in an ice water bath under nitrogen protection for 1 h to obtain a MXene suspension, which is then centrifuged (4200 rpm, 60 min) to obtain Ti3C2T x MXene dispersion;
[0064] (2) Synthesis of ZIF-8@MXene: 6.8 g of 2-methylimidazole (2-MIM) was added to 100 mL Ti3C2T x In the MXene dispersion, 15 mL of an aqueous solution containing 445 mg of Zn(NO3)2·6H2O was added to the above solution, stirred for 4 h, then washed with water and centrifuged (8000 rpm, 5 min), and freeze-dried at -60 °C for 30 h.
[0065] (3) Preparation of coated zinc anode: 120 mg ZIF-8@MXene and polyvinylidene fluoride (PVDF) prepared in step (2) were added to 300 μL N-methyl-2-pyrrolidone (NMP) solvent in a mass ratio of 9:1, then coated on zinc foil with a scraper and vacuum dried at 60 °C for 12 h to obtain a zinc electrode with a Z@M coating (Z@M-Zn), which was then cut into electrode sheets with a diameter of 10 mm using a slicer.
[0066] Comparative Example 1 :This comparative example provides a protective coating for zinc-iodine batteries and a preparation method thereof
[0067] The difference from Example 1 is that no ZIF-8 nanoparticles were added in this comparative example; the specific operation is as follows:
[0068] (1) The Ti3C2T x The MXene dispersion was freeze-dried at -60 °C for 30 h to obtain solid MXene two-dimensional nanosheets;
[0069] (2) Preparation of coated zinc anode: 120 mg of the prepared MXene two-dimensional nanosheets and polyvinylidene fluoride (PVDF) were added to 300 μL of N-methyl-2-pyrrolidone (NMP) solvent in a mass ratio of 9:1, then coated on zinc foil with a scraper and dried in vacuum at 60 °C for 12 h to obtain a zinc electrode with a MXene coating (MXene-Zn), which was then cut into electrode sheets with a diameter of 10 mm using a slicer.
[0070] Comparative Example 2 :This comparative example provides a protective coating for zinc-iodine batteries and a preparation method thereof
[0071] The difference from Example 1 is that Ti3C2T is not added in this comparative example. x MXene dispersion; the specific operation is:
[0072] (1) Synthesis of ZIF-8: 6.8 g of 2-MIM was added to 100 mL of water to dissolve, and 15 mL of an aqueous solution containing 445 mg of Zn(NO3)2·6H2O was added to the above solution, stirred for 4 h, then washed with water and centrifuged (8000 rpm, 5 min), and freeze-dried at -60 °C for 30 h to obtain ZIF-8;
[0073] (2) Preparation of coated zinc anode: 120 mg of the prepared ZIF-8 and polyvinylidene fluoride (PVDF) were added to 300 μL of N-methyl-2-pyrrolidone (NMP) solvent in a mass ratio of 9:1, then coated on zinc foil with a scraper and vacuum dried at 60 °C for 12 h to obtain a zinc electrode with a ZIF-8 coating (ZIF-8-Zn), which was then cut into electrode sheets with a diameter of 10 mm using a slicer.
[0074] Comparative Example 3 :This comparative example provides a protective coating for zinc-iodine batteries and a preparation method thereof
[0075] (1) Synthesis of Ti3C2T xMXene dispersion: Add 30 mL of 9M hydrochloric acid solution and 2 g of LiF powder to a polytetrafluoroethylene reaction container and mix thoroughly to form a uniform solution. Slowly add 1.5 g of Ti3AlC2 powder to the solution and keep it at 40 °C for 24 h. After etching, wash with ultrapure water until neutral and ultrasonicate in an ice water bath under nitrogen protection for 1 h to obtain a MXene suspension, which is then centrifuged (4200 rpm, 60 min) to obtain Ti3C2T x MXene dispersion;
[0076] (2) The Ti3C2T x The MXene dispersion was filtered using a 3501 diaphragm with a liquid volume of 50 ml, and then dried naturally at room temperature.
[0077] (3) Synthesizing a mixed solution: 6.8 g of 2-MIM was added to 100 mL of water to dissolve, and 15 mL of an aqueous solution containing 445 mg of Zn(NO3)2·6H2O was added to the above solution and mixed evenly;
[0078] (4) Synthesis of ZIF-8 / Ti3C2T x : The film obtained in step (2) is immersed in the mixed solution obtained in step (3) and stirred for 4 hours, then rinsed with water and dried at room temperature;
[0079] (5) Preparation of coated zinc anode: 120 mg ZIF-8@MXene and polyvinylidene fluoride (PVDF) prepared in step (4) were added to 300 μL N-methyl-2-pyrrolidone (NMP) solvent at a mass ratio of 9:1, and then coated on zinc foil with a scraper and dried in vacuum at 60 °C for 12 h to obtain a ZIF-8 / Ti3C2T4 negative electrode. x Coating (ZIF-8 / Ti3C2T x -Zn) and then cut it into electrode sheets with a diameter of 10 mm using a slicer.
[0080] Material Characterization:
[0081] like Figure 1 As shown in Figure 2, the Ti3AlC2 MAX precursor is a three-dimensional block with closely stacked layers to form obvious textures ( Figure 1 a); after etching and ultrasonic exfoliation, two-dimensional nanosheets were obtained ( Figure 1 b).
[0082] like Figure 2As shown, X-ray diffraction (XRD) analysis shows that the characteristic Al peak (104) disappears and the (002) crystal plane shifts significantly to the left, from 9.6° to 7.2°, thus confirming the successful synthesis of MXene.
[0083] like Figure 3 As shown, SEM and TEM images reveal that ZIF-8 nanoparticles are uniformly distributed on the MXene 2D nanosheets in the Z@M composite.
[0084] like Figure 4 As shown, the element distribution map shows that Ti, C, N and Zn elements are evenly distributed, which further verifies the uniform distribution of ZIF-8 on MXene.
[0085] Corrosion resistance test:
[0086] like Figure 5 As shown in Figure 2, the corrosion potential of Z@M-Zn (-0.972 V vs Ag / AgCl) is significantly higher than that of bare Zn (-0.983 V vs Ag / AgCl), MXene-Zn (-0.980 V vs Ag / AgCl), ZIF-8-Zn (-0.975 V vs Ag / AgCl), and ZIF-8 / Ti3C2T x -Zn (-0.978 V vs Ag / AgCl), and the corrosion current of Z@M-Zn (0.25 mA cm -2 ) is significantly lower than the other four electrodes (bare zinc is 2.1 mA cm -2 ,MXene-Zn is 1.58 mA cm -2 , ZIF-8-Zn is 0.65 mA cm -2 ,ZIF-8 / Ti3C2T x -Zn: 1.37 mA cm -2 ), therefore, the Z@M-Zn electrode prepared in the present application has the highest corrosion resistance.
[0087] The inventors have found that the change in the corrosion resistance of the coating is closely related to the structure, such as Figure 6 As shown in the figure, the contact angle test results show that MXene-Zn (75.8°), ZIF-8-Zn (69.8°) and ZIF-8 / Ti3C2T x -Zn (63.3°) is not much different from bare zinc (72.3°), but the contact angle changes significantly after the two are composited (95.6°), which increases significantly, indicating that the hydrophobicity of Z@M-Zn in the electrolyte is significantly enhanced, thereby improving the corrosion resistance.
[0088] Electrochemical performance test:
[0089] The cycle life of zinc negative electrode is related to discharge depth, current intensity, area capacity, electrolyte dosage, electrolyte additives, and surface modification strategies. Among the surface modification strategies, coating is an efficient method. Its conductivity, zinc affinity, hydrophobicity, corrosion resistance, stability, etc. are all related to the cycle life of zinc negative electrode. The extension of zinc negative electrode cycle life and the improvement of performance are the result of the combined effect of multiple properties.
[0090] (1) Figure 7 As shown, the linear sweep voltammetry (LSV) method was used to determine the characteristics of hydrogen evolution reaction. Zinc foil was used as the working electrode, Ag / AgCl was used as the reference electrode, and graphite rod was used as the counter electrode. Three-electrode test was carried out in 1M Na2SO4 solution.
[0091] The results show that compared with bare Zn (-1.651V vs Ag / AgCl), MXene-Zn (-1.742V vs Ag / AgCl), ZIF-8-Zn (-1.783V vs Ag / AgCl), ZIF-8 / Ti3C2T x -Zn (-1.687 V vs Ag / AgCl), at a current density of 5 mA cm -2 When , the hydrogen evolution potential of Z@M-Zn is more negative (-1.860 V vs Ag / AgCl), proving that it has a better hydrogen evolution inhibition effect.
[0092] (2) The zinc negative electrode sheet, iodine-doped polyaniline positive electrode sheet, electrolyte and separator prepared in Example 1 and Comparative Examples 1-2 were respectively assembled to obtain a symmetrical battery, an asymmetrical battery and a zinc-iodine full battery, wherein the symmetrical battery and the full battery used 2M ZnSO4 solution as the electrolyte, the asymmetric battery used 1M Na2SO4 solution as the electrolyte, and both used glass fiber GD as the separator.
[0093] like Figure 8 As shown, Cu foil is used as the positive electrode, bare zinc or modified zinc foil is used as the negative electrode, and the electrolyte is 1M Na2SO4. -2 , 1.5mAh cm -2 The coulombic efficiency test of the asymmetric battery was carried out under 400 ℃ and 800 ℃ conditions. Z@M-Zn showed high coulombic efficiency (99.93%) and good reversibility, with a cycle life of more than 1200 h.
[0094] like Fig.10 As shown, a symmetrical cell was assembled with two identical bare zinc or modified zinc foils as electrodes, and the electrolyte was 2M ZnSO4. -2 , 1mAh cm -2Long cycle tests were performed under 400 °C. Z@M-Zn exhibited a long cycle life of more than 1000 h and the best stability. In contrast, bare zinc short-circuited after only 100 hours of cycling due to the continuous growth of dendrites.
[0095] like Fig. 9 As shown in the figure, the Z@M negative electrode was assembled with the iodine-loaded PCM-NP positive electrode into a zinc-iodine battery, and electrochemical tests were performed in 2M ZnSO4 electrolyte. Compared with the 72.9% capacity retention of bare zinc, the capacity retention of the Z@M-Zn negative electrode after 2400 cycles was as high as 86.1%, showing stronger reversibility and cycle stability.
[0096] Among them, the synthesis of iodine-doped polyaniline positive electrode: 8mL phytic acid solution and 12mL water were mixed, and then 5mL aniline was added at 4°C. Subsequently, 0.96g ammonium persulfate was added to 5mL water and reacted at 4°C for 15h. After washing, the obtained product was pyrolyzed at a high temperature of 1000°C for 2h to obtain a black porous carbon material (PCM-NP) co-doped with N and P. Then 80mg PCM-NP was mixed with iodine at a mass ratio of 2:1 and heated at 120°C for 6h to obtain iodine-loaded PCM-NP.
[0097] Preparation of positive electrode sheet with iodine-loaded PCM-NP: 120 mg PCM-NP, acetylene black and polytetrafluoroethylene (PTFE) were mixed evenly in a mass ratio of 7.5:1.5:1, then rolled into electrode sheets, and finally cut into electrode sheets with a diameter of 10 mm using a slicer.
[0098] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. Application of an in-situ grown three-dimensional ZIF-8 / MXene composite material in the preparation of a zinc-iodine battery, wherein a slurry prepared from the composite material and a binder is attached to the surface of a zinc electrode as a protective coating; The composite material consists of MXene two-dimensional nanosheets and ZIF-8 nanoparticles, and the ZIF-8 nanoparticles are uniformly distributed on the MXene two-dimensional nanosheets.
2. The use according to claim 1, characterized in that The binder is selected from one or more of sodium carboxymethyl cellulose, styrene-butadiene rubber, polyacrylonitrile, polyvinyl alcohol, polytetrafluoroethylene, polyvinylidene fluoride, and polyimide; more preferably, the binder is polyvinylidene fluoride.
3. The use according to claim 1, characterized in that The method for preparing the in-situ grown three-dimensional ZIF-8 / MXene composite material comprises the following steps: S1, adding MAX powder into etching solution to perform etching reaction to obtain MXene dispersion; S2, adding ZIF-8 nanoparticles to the MXene dispersion to obtain a composite material; S3, mixing the composite material and the binder, coating the obtained slurry on the electrode sheet, and drying to obtain the slurry.
4. The use according to claim 3, characterized in that In step S1, the MAX powder is selected from one or more of Ti3AlC2, V2AlC and Nb2AlC; the etching solution is selected from one or more of HF, HCl and LiF; the temperature of the etching reaction is 30-50°C and the time is 12-36h; Preferably, the etching reaction temperature is 40°C and the time is 24h; Preferably, the mixture obtained after the etching reaction is washed with ultrapure water and subjected to ultrasonic stripping in sequence to obtain a MXene suspension, and then centrifuged to obtain a MXene dispersion; Wherein, the pH value of the mixture after washing with ultrapure water is neutral; The specific operation of the ultrasonic stripping is: under nitrogen protection, the neutral mixture after washing with ultrapure water is placed in an ice water bath and ultrasonicated for 0.8 to 1.2 hours; preferably, the ultrasonic time is 1 hour; The centrifugal speed is set at 3000-5000 rpm; preferably, the speed is set at 4200 rpm.
5. The use according to claim 3, characterized in that The MXene dispersion is freeze-dried to obtain solid MXene two-dimensional nanosheets; the freeze-drying temperature is -50 to -70°C, and the time is 20 to 50 hours; preferably, the freeze-drying temperature is -60°C, and the time is 30 hours.
6. The use according to claim 3, characterized in that In step S2, the ZIF-8 nanoparticles are prepared by mixing a 2-methylimidazole aqueous solution with a Zn(NO3)2·6H2O aqueous solution, and then washing, centrifuging, and freeze-drying in sequence; Wherein, the molar ratio of Zn(NO3)2·6H2O to 2-methylimidazole is 1:30 to 1:80; preferably, the molar ratio of Zn(NO3)2·6H2O to 2-methylimidazole is 1:50; The mixing reaction time is 2 to 5 hours; preferably, the mixing reaction time is 4 hours; The freeze-drying temperature is -50 to -70°C, and the time is 20 to 50 hours; preferably, the freeze-drying temperature is -60°C, and the time is 30 hours.
7. The use according to claim 3, characterized in that In step S2, the composite material is prepared by first adding 2-methylimidazole to a MXene dispersion, then mixing and reacting with a Zn(NO3)2·6H2O aqueous solution, and then washing, centrifuging, and freeze-drying in sequence; Wherein, the mass ratio of the MXene dispersion to 2-methylimidazole is 20:1 to 50:1; preferably, the mass ratio of the MXene dispersion to 2-methylimidazole is 35:1; The mixing reaction time is 2 to 5 hours; preferably, the mixing reaction time is 4 hours; The freeze-drying temperature is -50 to -70°C, and the time is 20 to 50 hours; preferably, the freeze-drying temperature is -60°C, and the time is 30 hours.
8. The use according to claim 3, characterized in that In step S3, the mixed composite material and binder are added to an organic solvent to form a slurry, which is then coated on the electrode sheet; preferably, the organic solvent is N-methyl-2-pyrrolidone; the mass ratio of the composite material to the binder is 10:1 to 8:1, preferably 9:1; The coating thickness is 10 μm, and a drying process is performed after coating, specifically: drying the coated electrode at 55 to 65° C. for 15 to 30 hours under vacuum conditions; preferably, drying the coated electrode at 60° C. for 24 hours; Preferably, the diameter of the electrode sheet is 8 to 10 mm, more preferably 10 mm.
9. A negative electrode of a battery, characterized in that: The battery negative electrode includes an in-situ grown three-dimensional ZIF-8 / MXene composite material and a binder; Preferably, the slurry prepared by the in-situ grown three-dimensional ZIF-8 / MXene composite material and the binder is coated on the zinc foil as a protective coating; the mass ratio of the composite material to the binder is 10:1 to 8:1, preferably 9:
1.
10. A zinc-iodine battery, characterized in that: A battery negative electrode comprising the battery negative electrode of claim 9, further comprising a positive electrode sheet, a separator and an electrolyte; Preferably, the preparation method of the positive electrode sheet is specifically as follows: aniline is added to a phytic acid aqueous solution, and an oxidant aqueous solution is added to the obtained aniline phytic acid aqueous solution to cause a polymerization reaction to obtain a black porous carbon material PCM-NP co-doped with N and P; then the PCM-NP is mixed with iodine for heating reaction to obtain iodine-loaded PCM-NP, which is mixed with a conductive agent and a binder and rolled into an electrode sheet to obtain; Wherein, the volume ratio of the phytic acid aqueous solution to aniline is 4:1, and the mass volume ratio of the aniline phytic acid aqueous solution to the oxidant is 5:1; The polymerization reaction temperature is 3-5°C and the reaction time is 12-36h; The product after the polymerization reaction is washed and then subjected to high-temperature pyrolysis, wherein the pyrolysis temperature is 800-1200° C. and the time is 1-5 hours; The mass ratio of the black porous carbon material PCM-NP to iodine is 1:1 to 4:1, preferably 2:1; The heating reaction temperature is 100-150°C and the time is 4-8h; The mass ratio of the iodine-loaded PCM-NP, the conductive agent and the binder is 7-8:1-2:0.8-1.2; preferably 7.5:1.5:1; Further preferably, the oxidant is any one of persulfate or peroxide; the persulfate is any one of ammonium persulfate, sodium persulfate, potassium persulfate, manganese persulfate, potassium hydrogen persulfate or potassium peroxymonosulfonate; and the peroxide is hydrogen peroxide or peracetic acid.
Citation Information
Patent Citations
Zinc ion battery negative electrode material and preparation and application thereof
CN111900388A
Zinc ion battery and method for improving cycle performance of zinc negative electrode of zinc ion battery
CN114142032A
Zinc ion battery negative electrode, preparation method thereof and zinc ion battery
CN115275083A
Vanadium-based MXene zinc negative electrode protective coating and zinc ion battery thereof
CN116799216A
Preparation method of single-few-layer Ti3C2Tx-loaded Fe-doped ZIF-8 derived carbon material
CN116936831A
Cited By
Battery monomer and preparation method thereof, battery device, power utilization device and energy storage device
CN122177900A